MicroRNA regulation of the bovine mammary immune response to a mastitis pathogen - Lawless, Nathan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
Bovine mastitis is an inflammation-driven disease of the mammary gland that is associated with €2 billion in yearly losses to the European dairy industry. Streptococcus uberis is now ranked amongst the most prevalent mastitis-causing pathogens throughout the EU and in North America. Mastitis develops when bacteria on entering the mammary gland, encounter mammary epithelial cells and resident monocytes, triggering local and systemic inflammation.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin